Pengaruh Return On Investment, Rasio Aktivitas, dan Ukuran Perusahaan Terhadap Kinerja Keuangan: Studi Kasus pada Sektor Industri Tekstil yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Mitta Viriyanti; Vicky Dzaky Cahaya Putra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to determine the effect of return on investment, activity ratio, and company size on financial performance (case study in the textile industry sector listed on the Indonesia Stock Exchange for the period 2019-2023. This research uses a quantitative approach. The data analyzed is secondary data taken from annual financial reports. The sampling technique used in this study was to use the Non-Probability Sampling method with Purposive Sampling. The population in this study were all textile industry sectors listed on the IDX for the 2019-2023 period consisting of 19 companies. The samples used in this study were 6 textile companies. Return on Investment (ROI) partially has a positive effect on financial performance, while the activity ratio partially has no significant effect on financial performance, and company size partially has no significant effect on financial performance. Return on Investment, activity ratio and company size simultaneously have a significant positive effect on financial performance.